Diurnal IOP-lowering efficacy and safety of travoprost 0.004% compared with tafluprost 0.0015% in patients with primary open-angle glaucoma or ocular hypertension - Schnober, Dietmar (Dove Medical Press, 2010)
PURPOSE: To compare the diurnal intraocular pressure (IOP)-lowering efficacy and safety of travoprost 0.004% and tafluprost 0.0015% administered to patients with primary open-angle glaucoma or ocular hypertension. METHODS: This was a randomized, double-masked, active-controlled, crossover design trial, in which patients were randomized to either travoprost or tafluprost monotherapy administered once daily in the evening for six weeks and then crossed over to the alternative treatment for another six weeks. Diurnal IOP was measured (8 am to 8 pm, every two hours) and a solicited symptom survey was administered at the end of both six-week periods, as was conjunctival hyperemia and visual acuity assessment, slit-lamp biomicroscopy, and adverse event solicitation. RESULTS: Fifty-one patients were randomized and 48 patients completed the study. The 12-hour mean diurnal IOP was significantly lower with travoprost therapy than with tafluprost therapy (P = 0.01), and a significantly lower IOP was also reported for travoprost at five of the seven individual time points (P < 0.05). Neither therapy produced a significant increase from baseline in any of the individual patient-reported symptom scores, except for hyperemia (P ≤ 0.01), which was increased with both treatments. Investigator-observed hyperemia was also increased from baseline with both therapies (P < 0.01), although the increase with travoprost therapy was significantly smaller than with tafluprost (P < 0.01). No additional safety concerns were noted from slit-lamp biomicroscopy or visual acuity results, and no difference was noted in patient-reported tolerability of the two medications. CONCLUSION: Travoprost 0.004% monotherapy produced lower diurnal IOP than tafluprost 0.0015% in patients with primary open-angle glaucoma or ocular hypertension and exhibited a similar safety profile.